DETERMINING OF THE TYPE OF MARKET OF ECOLOGICALLY CLEAN COSMETICS IN RUSSIA - MARINA VLADIMIROVNA Scherbina (Мир новой экономики, 2018)
Investigation of the concentration of monopoly power in the market of ecologically clean cosmetics has a great practical importance. It defines the structure of the market and, consequently, allows establishing the opportunity for new players to come into the market. Selection of the branch is not arbitrary. It has been determined byapromising branch.The emergence ofthe industrycaused bythe opening of newfast-growing companies. Moreover, the studyof market powerleads tosome interesting conclusions. When considering theHerfindahl- HirschmanandLernerresults are consistentandgive a completeandunambiguous picture. Authors spotted the structure ofthe barriers to entryandthe conditions forentry. The article will beusefulfor analystsspecializing inindustry analysis, as well asentrepreneurs who want tofind a nichein a market economy.